2018
DOI: 10.1038/s41467-018-05516-7
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial networks are less stable under drought than fungal networks

Abstract: Soil microbial communities play a crucial role in ecosystem functioning, but it is unknown how co-occurrence networks within these communities respond to disturbances such as climate extremes. This represents an important knowledge gap because changes in microbial networks could have implications for their functioning and vulnerability to future disturbances. Here, we show in grassland mesocosms that drought promotes destabilising properties in soil bacterial, but not fungal, co-occurrence networks, and that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
654
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,191 publications
(774 citation statements)
references
References 60 publications
61
654
7
1
Order By: Relevance
“…Altered root exudate composition may mobilize associated r‐strategist (bacterial‐dominated) microbial communities, in turn promoting microbial mineralization of N and facilitating plant regrowth (de Vries et al ., ). By contrast, slow‐growing plants with thicker, coarser roots are often more dependent on associations with mycorrhizal fungi (Ma et al ., ) and select for fungal‐dominated microbial communities that continue to function better under drought (de Vries et al ., , ). Thus, while slow‐growing plants are less affected by drought, root exudate‐facilitated rapid regrowth of exploitative species has the potential to outcompete slower‐growing species after drought, which leads to an increase in the abundance of exploitative species (de Vries et al ., ).…”
Section: A Hypothetical Framework For Understanding the Involvement Omentioning
confidence: 99%
See 2 more Smart Citations
“…Altered root exudate composition may mobilize associated r‐strategist (bacterial‐dominated) microbial communities, in turn promoting microbial mineralization of N and facilitating plant regrowth (de Vries et al ., ). By contrast, slow‐growing plants with thicker, coarser roots are often more dependent on associations with mycorrhizal fungi (Ma et al ., ) and select for fungal‐dominated microbial communities that continue to function better under drought (de Vries et al ., , ). Thus, while slow‐growing plants are less affected by drought, root exudate‐facilitated rapid regrowth of exploitative species has the potential to outcompete slower‐growing species after drought, which leads to an increase in the abundance of exploitative species (de Vries et al ., ).…”
Section: A Hypothetical Framework For Understanding the Involvement Omentioning
confidence: 99%
“…By contrast, slow‐growing plants with thicker, coarser roots are often more dependent on associations with mycorrhizal fungi (Ma et al ., ) and select for fungal‐dominated microbial communities that continue to function better under drought (de Vries et al ., , ). Thus, while slow‐growing plants are less affected by drought, root exudate‐facilitated rapid regrowth of exploitative species has the potential to outcompete slower‐growing species after drought, which leads to an increase in the abundance of exploitative species (de Vries et al ., ). Changes in root exudation quantity and quality after drought can also lead to increased decomposition of soil organic C (priming) and contribute to the sharp peak in CO 2 production when soil is rewetted (the ‘Birch effect’; Birch, ).…”
Section: A Hypothetical Framework For Understanding the Involvement Omentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that drought can strongly affect plant growth and soil microbial community activity and composition, resulting in altered rates of C and N cycling processes (Gordon et al ., ; Sanaullah et al ., ; De Vries et al ., , ; de Nijs et al ., ). Similar to elevated CO 2 and grazing, root exudates have been hypothesized to play an important role in the response of soil microbial communities to drought, but it is challenging to disentangle root‐exudate‐mediated effects from other mechanisms through which drought affects soil microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…However, some researchers have found that microbial composition was very important to the ecosystem processes, especially for the process rates (Aalto, Saarenheimo, Mikkonen, Rissanen, & Tiirola, ; Allison & Martiny, ; Baho, Peter, & Tranvik, ; Galand et al, ). Interestingly, de Vries et al () demonstrated that the bacterial community was not associated with ecosystem respiration under drought conditions, but was directly associated with ecosystem respiration after 1 week of rewetting.…”
Section: Discussionmentioning
confidence: 99%